Photo‐Fenton and Fenton Oxidation of Recalcitrant Wastewater from the Wooden Floor Industry. (1st June 2015) - Hansson, Henrik; Kaczala, Fabio; Marques, Marcia; Hogland, William
ABSTRACT: : There is a need for development of on‐site wastewater treatment technologies suitable to "dry‐process" industries, such as the wooden floor sector. Due to the nature of their activities, these industries generate low volumes of highly polluted and recalcitrant wastewaters due to washing and cleaning surfaces and machinery. Advanced oxidation processes such as Fenton and photo‐Fenton are potentially feasible options for the treatment of wastewaters with not easily biodegradable pollutants. The wastewater from a wooden floor industry with initial COD value of 4956 mg/L and TOC value of 2730 mg/L was treated with Fenton (Fe/H2 O2 ) and photo‐Fenton (Fe/H2 O2 /UV) applying a 2‐level full‐factorial experimental design. The highest removals of COD and TOC (79% and 62% respectively) were achieved when photo‐Fenton was applied. In conclusion, Fenton and photo‐Fenton are promising treatment options for these highly recalcitrant wastewaters, photo‐Fenton being a more promising option according to the results.